2011
DOI: 10.1007/s11430-011-4238-6
|View full text |Cite
|
Sign up to set email alerts
|

Holocene delta evolution and sequence stratigraphy of the Pearl River Delta in South China

Abstract: We analyzed the sedimentary characteristics and chronostratigraphy of the Pearl River Delta in South China, and discussed the Holocene stratigraphic characteristics and the filling process since the Holocene, based on 90 boreholes. Our results showed that the maximum transgressive surface of the Pearl River Delta was located in the soft marine silt horizons, whereas it was shown as an erosion surface in areas with tidal scour. From bottom to top, Holocene sedimentary sequences were fluvial facies, floodplain-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 24 publications
(22 reference statements)
4
31
0
Order By: Relevance
“…This rate fits in well with the rates of 0.8-1.0 mm yr À1 during 7.84-3.95 kyr BP (Owen et al, 1998). Similarly, Wei and Wu (2011) showed that the average accumulation rate for the Holocene was 1.3 mm yr À1 at the time of 10.0-7.5 kyr BP, 2.3 mm yr À1 for the period of 7.5-5.0 kyr BP, 1.9 mm yr À1 between 5.0 and 2.5 kyr BP, and 2.3 mm yr À1 thereafter over the entire Pearl delta. Huang et al (1983) obtained slightly different rates, i.e., 2.7 mm yr À1 during 7.5-5.0 kyr BP, 2.2 mm yr À1 for the period of 5.0-2.5 kyr BP, and 2.2 mm yr À1 thereafter.…”
Section: Deposition Ratessupporting
confidence: 80%
“…This rate fits in well with the rates of 0.8-1.0 mm yr À1 during 7.84-3.95 kyr BP (Owen et al, 1998). Similarly, Wei and Wu (2011) showed that the average accumulation rate for the Holocene was 1.3 mm yr À1 at the time of 10.0-7.5 kyr BP, 2.3 mm yr À1 for the period of 7.5-5.0 kyr BP, 1.9 mm yr À1 between 5.0 and 2.5 kyr BP, and 2.3 mm yr À1 thereafter over the entire Pearl delta. Huang et al (1983) obtained slightly different rates, i.e., 2.7 mm yr À1 during 7.5-5.0 kyr BP, 2.2 mm yr À1 for the period of 5.0-2.5 kyr BP, and 2.2 mm yr À1 thereafter.…”
Section: Deposition Ratessupporting
confidence: 80%
“…At the river mouth, the Pearl River delta has prograded at an average rate of 17 m/yr over the past 6,000 years (Huang and Song, 1981;Fyfe et al, 1999). The present Pearl River delta is confined within the estuary of the river (Wei and Wu, 2011;Wu et al, 2014).…”
Section: Geological Settingmentioning
confidence: 99%
“…3A and C). Nowadays, the Pearl River delta is confined in the estuary of the Pearl River (Wei and Wu, 2011), and the outer shelf is covered with sand waves (Wang, 2000;Zhuo et al, 2014).…”
Section: Sea Level Change Sediment Supply and Continental Margin Shapementioning
confidence: 99%